Antimicrobial resistance and putative virulence genes of Pseudomonas aeruginosa isolates from patients with respiratory tract infection - Al Dawodeyah, Heba Y; Obeidat, Nathir; Abu-Qatouseh, Luay F; Shehabi, Asem A (Germs (Bucureşti), 2018)
is a common agent causing community acquired and nosocomial respiratory tract infections, with particularly life-threatening manifestations in patients who are immunocompromised of who have cystic fibrosis. This study investigated the occurrence of extended-spectrum β-lactamases (ESBLs) and metallo β-lactamase (MBL) in association with important putative virulence genes and genotypes variation among isolates from respiratory tract infection of Jordanian patients. Over a period of 8-month, a total of 284 respiratory tract samples were obtained from patients diagnosed with respiratory tract infection while attending the Pulmonary Clinic/Intensive Care Unit, Jordan University Hospital (JUH). At the time of sampling most were inpatients (86.9%). Samples were cultured specifically for . A total of 61/284 (21.5%) isolates were recovered from respiratory samples of patients. The percentage of MDR isolates was 52.5%, and all isolates were susceptible to colistin with lower rates of susceptibility to other tested antibiotics. Positive genes of , , , and were detected in 68.9%, 18.9%, 18.9%, 15.6% and 12.5% of isolates, respectively. Genotyping revealed no significant genetic relationship among MDR isolates from hospitalized patients as judged by the constructed dendrogram and the presence of 14 genotypic groups. The percentages of the virulence genes , , , , and among isolates were 98%, 98%, 80%, 33% and 33%, respectively, and 87% of isolates produced pyocyanin. The present study demonstrates high occurrence of MDR isolates carrying genes. No specific associations were found between antibiotic resistance, virulence genes and genotypes among MDR isolates.